Food and farming - Baines, John D. (The global village, 2008)
Investigates the effects of globalisation on key international issues. This book addresses questions such as: Are traditional skills, cultures and systems being lost in the interests of worldwide trade and economic progress? Can a balance be achieved between the expansion of global activities and preserving the interests of individual countries?